A privatização do sistema prisional - Mauricio, Célia Regina Nilander (2011)
The prison sentence that resists time and governments, and the whole society criticism, that empirically transcends a desolation scenario imprisoning human beings and treating them cruelly and inhumanely, behind concrete and iron walls in a place where the concept of resocialization is practically inexistent. It is still one of the biggest problems currently faced by the State, which does not comply with some criminalization orders contained in Brazilian Constitution, namely: citizenship principle, equality principle and, essentially, human being dignity principle. However, on contemporary globalized world, many services that were performed by the State exclusively are also performed by particular now and, more recently, such phenomenon reached prison management bringing us an innovative and promising concept on prison law scope, by means of public private partnerships. This study shows us how such new prison management proposal is occurring on other countries, as well as Brazilian experiments results and the problem involving that issue on legal, ethical, and political scope